Challenges and Support Strategies for Orphaned Children and Youth in Kazakhstan: A Comprehensive Evaluation of the Youth House Program - Medyanov Arislambek (Scientific Research and Experimental Development, 2024)
This study examines the challenges faced by orphaned children and youth in Kazakhstan and evaluates the impact of various support programs implemented by organizations such as the Youth House, a subdivision of SOS Children's Village. Orphaned youth often experience psychological distress, limited educational opportunities, and difficulties in achieving personal and professional development. The Youth House employs a comprehensive approach, including religious awareness training, habit-breaking workshops, psychological games, career orientation training, and individual counseling to address these needs. The results indicate significant improvements in the youths' critical thinking, communication skills, and overall psychological maturity. The interventions have also led to a decrease in harmful behaviors such as smoking and substance abuse. Despite these successes, several limitations were identified, including resource constraints, infrastructural issues, limited availability of mental health professionals, and a lack of long-term follow-up mechanisms. To address these limitations, the study proposes increased funding, infrastructure development, enhanced psychological support, implementation of long-term monitoring systems, and stronger community engagement. The findings underscore the importance of comprehensive and sustained support for the successful integration of orphaned children and youth into society. This research contributes to the understanding of effective strategies for supporting vulnerable orphaned youth in Kazakhstan and highlights the need for continued efforts and resources to improve their outcomes.